SUAKA DIPLOMATIK DALAM KAJIAN HUKUM INTERNASIONAL - Lucia Ch. O. Tahamata (SASI, 2011)
Asylum problem is oftentimes assumed to represent the political problem, though represent the law problem special of international law diplomatic asylum is asylum which. Asylum is asylum which give to one who ask the protection of below diplomatic delegation of foreign state. Problem which emerge is whether people on who request asylum the foreign embassy region can be given by a diplomatic asylum. This writing is diplomatic debate asylum evaluate the international law and to present practice the states in diplomatic asylum give